The general's daughter - West, Simon; Goldman, William, 1931-; Krane, Jonathan D.; Neufeld, Mace; Rehme, Robert ([California] : Paramount Pictures, 1999)
When the daughter of a well-known and well-respected base commander is raped and murdered, an undercover detective is summoned to look into the matter and finds a slew of cover-ups at West Point
Title from title screen
Editor, Glen Scantlebury ; music, Carter Burwell ; cinematographer, Peter Menzies, Jr.
Cast: John Travolta, Madellene Stowe, James Cromwell, Timothy Hutton, Clarence Williams II, James Woods
DVD Format
In English or Thai with optional English, Cantonese, Mandarin, Thai, or Korean subtitles
Keywords: Detective -- Drama; Murder -- Drama